Mythology Creation in Aluk Todolo as Reference to Perceive Women’s Role in the Toraja Church - Johana Ruadjanna Tangirerung (KINAA: Jurnal Teologi, 2016)
Abstrak The role of women in life ancestor of Toraja, culturaly is very important. There are many position and role that ocupay women in society. There are also many methapore that can be identify in Toraja culture. That mean women in Toraja is very important. Meanwhile in reality in society even in church the role of women is going to decrease. This article will explore this situation, will looking for what is caused this situation changes. One of methapore is mythology of ancestor creation. In this mythology women taken a importan role, so that this metaphore can propose the indispensable of women in Toraja Churc. The aim of this article is to open of all chance for women leadership in society and in the church. Key Words: Mythology, role, Church, culture, women